PENGARUH MEDIA KOKORU TERHADAP KEMAMPUAN MOTORIK HALUS ANAK KELOMPOK B DI TK MUSLIMAT NURUL HUDA KECAMATAN SEKARAN KABUPATEN LAMONGAN - Retno Dwi Astuti; Anisa Yunita Sari (JCE (Journal of Childhood Education), 2018)
The purpose in This Quasi Experimental Design design research to prove whether kokoru media has an effect on the fine motor skills of group B children in TK Muslimat Nurul Huda. The study populationÂ  were children B group of TK Muslimat Nurul Huda with sample of 20 children in group B1 and 20 childrenÂ  in group B2. Technique of collecting data using observation and documentation methods. Test data analysis using Mann Whitney U test with the formula Ucount<Utable (Î±=0,05). From the data processing then obtained Ucount =22 dan Utable 114, it indicated that Ho is rejected and Ha accepted. Based on the above test it can be concluded that kokoru media have an effect on the fine motor skills of group B children in TK Muslimat Nurul Huda